Some Questions and Challenges in Measurements of Solar Magnetic Fields - Hongqi Zhang; Jiangtao Su; Xiaofan Wang; Xingming Bao; Yu Liu; Yingzi Sun; Mingyu Zhao (Universe)
Huairou Solar Observing Station of the National Astronomical Observatories of Chinese Academy of Sciences has been in operation since 1987. During its operation, successful observations of the solar vector magnetic field have been conducted. On the basis of the achievements at Huairou, we analyze the methods of observing the solar magnetic field, including discussions of the approximation of the transfer theory of the solar magnetic field in the atmosphere, wide field of view polarized observation, and some questions on the inversion of solar magnetic field data. We also present relevant challenges for further research.